Comparison the Serum Level of Paraoxonase Activity in Frequent Relapse and Infrequent Relapse Patients with Nephrotic Syndrome - Dhuha A. Hussain; Sinan A. Ibrahim; Raid J. Mohamed (Indian Journal of Forensic Medicine & Toxicology, 2021)
Nephrotic syndrome (NS) is distinguished by heavy proteinuria (urine protein:creatinine ratio ?2000 mg/gor ?300 mg/dL, or 3+ protein on urine dipstick), hypoalbuminemia (?2.5 g/dL), and edema. Leakage ofmassive amounts of serum proteins into the urine leads to a hypercoagulable state, a higher rate of infectiousdisease, and the dysregulation of fluid balance. Idiopathic nephrotic syndrome (INS)is one of the most common renal problems in children encountered in day-to-day nephrology practices.The present study was aimed to evaluate the oxidant/ antioxidant status by measuring paraoxonase (PON)activities as well as total antioxidant capacity in steroid sensitive nephrotic syndrome (frequent and infrequentrelapse) and compares it with healthy control children . Paraoxonase activity by spectrophotometer in threegroups consisted of age and sex matched (30) patients with Frequent relapse nephrotic syndrome FRNS ,(30) patients with infrequent relapse nephrotic syndrome (IFRNS) and (30) healthy control children. Theserum level of paraoxonase activity in infrequent relapse group was 101.61±43.0 IU which far less thanfrequent relapse group (160.44±44.22 IU) or controls (228.35±32.35 IU) with highly significant differences.Of note, the difference between control group and frequent relapse group was highly significant.